Human Rights in the Indonesian Constitutional System Post-Amendment of the 1945 Constitution - Kimico Margaretha Tjhia; Faisal Santiago; Tina Amelia (Siber Nusantara of Law and Politic Review, 2026)
The 1999–2002 amendments to the 1945 Constitution marked a significant transformation in Indonesia's constitutional framework, particularly with the inclusion of Chapter XA on Human Rights. This chapter contains a comprehensive catalogue of rights, civil, political, economic, social, and cultural, textually adopting norms from the Universal Declaration of Human Rights and the International Covenant on Civil and Political Rights. This study aims to analyze these constitutional changes from a rights-based constitutionalism perspective and examine the gap between constitutional norms and the practical implementation of human rights in Indonesia. Using a normative-analytical approach and comparative constitutional law, this research finds that, while Indonesia's human rights catalogue aligns with international standards, its implementation still faces serious challenges, such as a low Fundamental Rights score (0.54) according to the World Justice Project (2023), and inconsistent judicial rulings. Comparative analysis reveals that Indonesia stands between the Philippines' strict scrutiny model and South Africa's transformative constitutionalism. The study recommends strengthening constitutional review standards, enhancing the capacity of non-judicial institutions, and integrating human rights education into national policy.